2016
DOI: 10.12659/msm.895771
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Interleukin-1β-511 C/T Polymorphism and Gastric Cancer in Chinese Populations: A Meta-Analysis

Abstract: BackgroundSeveral studies have indicated that interleukin (IL)-1β-511 C/T polymorphism may contribute to individual susceptibility to gastric cancer, but the results vary among regions and races. No relevant meta-analysis has been conducted in a Chinese population. Therefore, we performed the current meta-analysis to investigate the possible correlation between IL-1β-511 C/T polymorphism and gastric cancer susceptibility in Chinese subjects.Material/MethodsPubMed, EmBase, Cochrane Library, Chinese Biology Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…A meta-analysis of available data presents the precise estimation of the effects of the polymorphisms. Previous meta-analyses showed that IL1β polymorphisms affect the risk of various clinical conditions and cancers ( 46 - 48 ). However, to this date, no meta-analysis study has reported a precise correlation between IL1β polymorphisms and the risk of gestational disorders.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of available data presents the precise estimation of the effects of the polymorphisms. Previous meta-analyses showed that IL1β polymorphisms affect the risk of various clinical conditions and cancers ( 46 - 48 ). However, to this date, no meta-analysis study has reported a precise correlation between IL1β polymorphisms and the risk of gestational disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The results of Rokkas et al [23] meta-analysis showed similar results: their pooled OR of H. pylori infection, AG, and IM between individuals with family history of GC were 1.92-fold (p ≤ 0:001), 2.2-fold (p = 0:005), and 1.98-fold (p ≤ 0:001) higher, respectively, in comparison with controls. These results can be influenced by the exposition of shared environmental factors (alcohol, smoking, salted and smoked food, and hygiene) between family members, circulation of intrafamilial H. pylori strains [24][25][26], and genetic susceptibility [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] For example, in meta-analysis studies, a strong synergistic interaction between IL-1β polymorphisms and H. pylori infection in the development of gastric cancer was detected. [14][15][16][17][18] In addition, an association between IL-1β polymorphisms and H. pylori infection was reported in Asian, European, and Latin American populations. [19][20][21][22][23][24] Polymorphisms in IL-1B have also been shown to influence the responses to H. pylori triple therapy in different populations including American, [25][26][27] Japanese, [28][29][30] and Korean.…”
Section: Introductionmentioning
confidence: 99%